Stake Net Fishery of Central Kerala – Costs, Returns and Seasonality: Stake Net Fisheries: Economics and Seasonality - V., Geethalakshmi; V. Chandrasekar; Nikita Gopal (Fishery Technology, 2024)
Stake net fishing in Vembanad Lake plays a vital role in the local economy and to food security. The study analysed the cost and return and seasonality of stake net fishery in Vembanad Lake, Kerala, India. It faces significant challenges threatening its sustainability. High-value prawns comprise of 65% of landings from fishery and account for more than 70% of the revenue realisation. The annual net profit is less than Rs.2 lakhs per stake net unit which again is shared among the crew of 3 to 4 members, which is only nominal considering the fishing effort. The average catch during lean months is currently reported to be as low as 9.49 kg per unit. The net present value of stake net fishing unit was computed as Rs.10.26 lakhs. The study points to seasonality in fish landings.